2022
DOI: 10.2196/33704
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Long COVID-19 on Mental Health: Observational 6-Month Follow-Up Study

Abstract: Background The psychological impact of COVID-19 can be substantial. However, knowledge about long-term psychological outcomes in patients with COVID-19 is scarce. Objective In this longitudinal, observational study, we aimed to reveal symptoms of posttraumatic stress disorder (PTSD) and symptoms of anxiety and depression up to 6 months after the onset of COVID-19–related symptoms in patients with confirmed COVID-19 and persistent complaints. To demonstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 49 publications
3
65
0
1
Order By: Relevance
“…In the present study patients with LCS showed high values of anxiety, depression and sleep disturbances, in line with recent reports [41] , [42] , [43] , [44] , [45] . After the MDR program we highlighted high improvements in self-related anxiety and depression levels.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study patients with LCS showed high values of anxiety, depression and sleep disturbances, in line with recent reports [41] , [42] , [43] , [44] , [45] . After the MDR program we highlighted high improvements in self-related anxiety and depression levels.…”
Section: Discussionsupporting
confidence: 93%
“…We speculate that improvement of ED could be explained by gradual recuperation of physical competency. Apart from ED, other symptoms during COVID-19 infection, including mental health, anosmia and ageusia, were also significantly improved after three months of infection [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is key to note the relationship between CT-SS and "emotional functions", suggesting that an impaired clinical and radiological scenario might lead to anxiety, sadness, and anger in the acute setting. This issue has not been as well investigated in acute patients as it has in patients with long-COVID syndrome 22 and discharged patients. 23 Patients affected by COVID-19 complain of several signs and symptoms involving systems other than the respiratory system.…”
Section: Discussionmentioning
confidence: 99%